Perwujudan Hidup Kontemplatif Menurut Santa Clara Assisi dalam Persaudaraan Suster Claris Capusines Masa Kini - Sergius Lay; Fidelis Samosir (Jurnal Magistra, 2024)
This research is a literature review and aims to explore various literature of the Order of Clare Capuchins and reflect on the challenges and opportunities to live the characteristics of contemplative life in the present. as for the challenges of contemplative life at this time are experiencing an identity crisis, a crisis of appreciation of faith, pride, and dealing with scientific and technological advances. The way to face these challenges is through discernment, persevering in prayer, meditating on the word of God, realizing the work of the Holy Spirit, living in the presence of God, daring to enter silence, living joy, having humility, remaining patient and living simply.